Statistics for food scientists : making sense of the numbers - Rossi, Frank; Mirtchev, Victor (Elsevier, 2016)
The practical approached championed in this book have led to increasing the quality on many successful products through providing a better understanding of consumer needs, current product and process performance and a desired future state. In 2009, Frank Rossi and Viktor Mirtchev brought their practical statistical thinking forward and created the course "Statistics for Food Scientists". The intent of the course was to help product and process developers increase the probability of their project's success through the incorporation of practical statistical thinking in their challenges. The course has since grown and has become the basis of this book.